Thakur’s Iterative Scheme for Approximating Common Fixed Points to a Pair of Relatively Nonexpansive Mappings - R. Gopi; V. Pragadeeswarar; M. De La Sen (Journal of Mathematics)
In this work, we propose the three-step Thakur iterative process associated with two mappings in the setting of Banach space. Using this Thakur iteration, we approximate a common fixed point for a pair of noncyclic, relatively nonexpansive mappings. And we support our main result with a numerical example. Also, we give a stronger version of our main result by using von Neumann sequences. Finally, we provide some corollaries on the convergence of common best proximity points in uniformly convex Banach space.